Computational investigation of ginkgetin and theaflavin as potential inhibitors of heat shock protein 90 (Hsp90). Issue 24 (26th December 2022) - Bhadresha, Kinjal; Upadhyay, Vinal; Kumar, Sivakumar Prasanth; Pandya, Pujan; Jain, Nayan; Rawal, Rakesh M.
Abstract: Heat shock protein 90 (Hsp90) is the prime molecular chaperone found to be overexpressed in cancer cells and pose as an anti-cancer therapeutic drug target for cancer chemotherapy. Even drugs are available which inhibit Hsp90, the associated side effects along with multi-drug regimen necessitate the identification of natural molecules to block the activity of Hsp90. In this present investigation, we performed virtual screening of Hsp90 inhibitors from a curated collection of natural molecules with proven pharmacological effects. This process helped in the identification of the top two scoring ligands, ginkgetin and theaflavin with favorable as well as crucial interactions with the Hsp90 ligand-binding pocket. Molecular dynamics simulations of these two natural molecules exhibited minimal fluctuations in the binding pattern of ginkgetin and theaflavin to Hsp90 which retained crucial contacts throughout the simulation time. We anticipate that ginkgetin and theaflavin could act as potent Hsp90 inhibitors which are under current investigation in our laboratory. Communicated by Ramaswamy H. Sarma